Education at a glance 2014 : OECD indicators - (:unkn) unknown (OECD Publishing, 2014)
This annual OECD study "is the authoritative source for accurate and relevant information on the state of education around the world. It provides data on the structure, finances, and performance of education systems in the OECD's 34 member countries, as well as a number of partner countries." The 2014 edition includes new indicators on private institutions, on what it takes to become a teacher, and on the availability of, and participation in, professional development activities for teachers. Furthermore, data from the 2012 Survey of Adult Skills, a product of the OECD Programme for the International Assessment of Adult Competencies (PIAAC), on attainment, employment, intergenerational education mobility, earnings, and social outcomes related to skills proficiency, is provided. (Publisher, BIBB-Doku)

Contents: Chapter A. The output of educational institutions and the impact of learning Chapter B. Financial and human resources invested in education Chapter C. Access to education, participation and progression Chapter D. The learning environment and organisation of schools
Keywords: G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 1.2.2.4 Arbeitslosigkeit; S 1 Stufen der Berufsbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.1 Finanzierungsquellen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 1.5 International vergleichende Berufsbildungsforschung; Wirtschaftskrise; Jugendarbeitslosigkeit; Bildungssystem; Effizienz; Indikatoren; Bildungsniveau; Bildungsökonomie; Bildungsertrag; Bildungsinvestition; Bildungsausgaben; Bildungsbeteiligung; Bildungsverlauf; Lernbedingungen; Bildungsstatistik; Quantitative Angaben; Internationaler Vergleich; OECD-Staaten